(untitled) (The International Journal for Scientific Research, 2025)
The aim of this research is to explore the practices of digital knowledge management for tangible heritage through a case study of the Sharjah Antiquities Authority. It stems from the growing need for practical solutions that enhance the management of the digital lifecycle of tangible heritage collections, including creation, description, organization, preservation, and digital display. The study adopts a descriptive-analytical approach supported by a case study methodology, utilizing semi-structured interviews and official documents, including policies, plans, and reports, alongside analysis of digital platforms and direct observation. The findings indicate that the Authority implements an integrated digital knowledge management model, from digitization to dissemination, based on standardized descriptive metadata and file formats, supported by a robust digital infrastructure and an advanced digital asset management system. Moreover, the Authority applies a long-term digital preservation strategy, including multi-site backups, format migration, and integrity checks, while providing access to content through diverse digital platforms designed to meet the needs of various user groups. The study also identifies key challenges, such as difficulties in capturing the tangible and intangible properties of artifacts during digitization, alongside the need for specialized skills and sufficient financial resources. Accordingly, the study recommends enhancing community engagement through participatory initiatives, employing artificial intelligence techniques for data creation and image analysis, strengthening the evaluation framework of digital platforms beyond visitor counts to include their impact on learning and heritage awareness, and establishing partnerships with universities while investing in human capacity building to achieve self-sufficiency in digitization processes.